Improving Literacy and Minahasan Cultural Values through Folklore Reading to Paniki Bawah’s Children Residents - Kobis, Dewi Christa; Sigarlaki, Stephani; Pamantung, Rina (Universitas Teknokrat Indonesia, 2024)
The project of public service implemented for this study aimed to improve literacy and Minahasan cultural values through folklore reading. The participants of this public service were 20 poverty-stricken children who lived in Paniki Bawah sub-district located in Manado, North Sulawesi. Before the public service project was implemented, the majority of them were only in the Word Level of literacy level and had zero knowledge about Minahasa folklore. However, after the public service implementation, most of the participants reached the highest level of literacy level, which is called Story 2 Level where they could rewrite their stories by paraphrasing them into their own words but did not eliminate any content of the folklores. This public service project was considered a successful movement and able to improve the participants’ literacy as well as their Minahasan cultural values.